Automatized Calculating System for a Ketogenic Diet: CETORAP - Ligia M. Marcos Plasencia; Edelsia Rojas Massipe; Amarilis Barbié Rubiera (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
Fundament: The refractory epilepsy when being treated with antiepileptic drugs is one of the problems faced by Neurologists specialized in the Pediatric Branch. There are some experiences in the usage of ketogenic diet in these cases, but with the difficulty that brings about the process of calculating recommendations on energy and macronutrients which is involved in this alimentary special regimen. Objective: To create a reliable and fast method to accelerate the bothersome and lingerie calculations of the necessary recommendations for a ketogenic diet. Methods: A list of allowable food for alimentary regimen with the required quantity of energy and macronutrients contains in portions was created and used as a data base for an automatized system of recommended calculation according to the age and sex of the patient and, in a second period was used for the calculation of the pattern. Within this, recipes of appropriate dishes for ketogenics menu were created. Results: An interactive system of easy management was created to allow the pertinent calculations for a ketogenic regimen in a given patient and in very short period of time. This system has been put into practice in the National Institute of Neurology and Neurosurgery with notable savings regarding time and reliability of the estimations in terms of energy and food. Its simplicity permits the usage of different levels of technicians (dieticians) and professionals. Conclusions: The created system gives possibilities to make ketogenic diet which contributes to keep health on epileptic patients.